Music Therapy and Shaping to Increase Communication Skills of Visual Impair Child With Specifi Language Impairment - Farida Kurniawati; Karina Adistiana (Universitas Islam Indonesia, 2011)
The study was carried out to investigate the effectivity of combination of behavioral music therapy and shaping on communication skill development of visual impairment child with specific language impairment (SLI). The program consisted of three stages and evaluation session. The findings show significant improvement of communication skill of the ten year old girl participant She expresses her desire to eat using the song